LANGO ACTIVISM (LEGAL AID NGOS) ON THE RISE OF NEOLIBERAL GOVERNMENTALITY IN POST-AUTHORITARIAN INDONESIA: EXAMINING TWO DECADES OF STRUGGLE - Andreas Budi Widyanta; Heru Nugroho; Arie Sujito (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
This paper analyzes the dynamics and challenges of the movement of a Legal Aid NGO (LANGO) in Indonesia in advocating for the rights of the weak, poor, and marginalized to gain access to justice during two decades of reform. Through historical, sociological, and political insights, this paper reveals the discursive narrative of neoliberal governmentality for the last twenty years. This study uses a qualitative method, with data collection techniques of observation, documentation, and in-depth interviews with three informants from Legal Aid NGO. Using the Foucaultian analytical framework, this study finds that neoliberal governance has shaped LANGO as a managerial subject that implicitly and obediently promotes the discourse and practice of neoliberal rationality. But on the other hand, LANGO becomes an administrative subject resistant to neoliberal rationality by performing several maneuvers and tactics: promotion, contextual adaptation, avoidance/avoidance, and rejection. This contradiction and ambivalence become a severe challenge for LANGO in realizing equal access to justice for the marginalized and vulnerable in Indonesia.Paper ini akan menganalisis secara kritis dinamika dan tantangan gerakan dari sebuah Legal Aid NGO (LANGO) di Indonesia dalam mengadvokasi hak-hak kaum lemah, miskin, dan terpinggirkan untuk mendapatkan akses keadilan selama dua dekade reformasi. Melalui tilikan historis, sosiologis, dan politis, paper ini akan mengungkap narasi diskursif governmentality neoliberal yang berlangsung selama dua puluh tahun terakhir. Penelitian ini menggunakan metode kualitatif dengan teknik pengumpulan data berupa observasi, dokumentasi, dan wawancara mendalam terhadap tiga informan dari Legal Aid NGO. Dengan menggunakan kerangka analisis Foucaultian, studi ini menemukan bahwa pemerintahan neoliberal telah membentuk LANGO sebagai subjek manajerial yang secara implisit dan patuh mempromosikan wacana dan praktik rasionalitas neoliberal. Namun di sisi lain, LANGO menjadi subjek manajerial yang resisten terhadap rasionalitas neoliberal dengan melakukan sejumlah manuver dan taktik: promosi, adaptasi kontekstual, penghindaran, dan penolakan. Kontradiksi dan ambivalensi ini merupakan tantangan serius bagi LANGO dalam mewujudkan kesetaraan akses keadilan bagi kaum marginal dan rentan di Indonesia.